Tatiana Zalahar Podolinská: Marian Devotion Among the Roma in Slovakia: A Post-Modern Religious Response to Marginality: Cham: Palgrave Macmillan, 2021, 166 s., ISBN: 978-3-030-56364-6 - Spalová, Barbora (Romano džaniben, 2022)
RECENZE